The effectiveness of the Zimbabwe Republic Police Criminal Investigation Department in curbing drug abuse among youths in Zimbabwe: a case of Mbare - Makande, Nancy A. (Midlands State University, 2018)
This study seeks to assess the effectiveness of the ZRP,CID, Drugs and Narcotics department in dealing with drug abuse issues in Zimbabwe. The study used the case study of Mbare for the research. This is because Mbare is ranked highest in drug abuse cases in Zimbabwe. The study sought to uncover the nature of drug abuse in Zimbabwe and establish causes and effects of drug abuse. The study found unemployment and peer pressure among the major cause of drug abuse. The effects of drug abuse cut across health issues, social, political and economic effects. The study also sought to establish the role that the security department plays I curbing drug abuse in Zimbabwe and what they are doing in efforts to curb abuse of drugs. These include raiding and arresting drug law offenders, awareness raising in communities and patrols in communities in civilian clothing. The study goes on to look at the strengths, weakness and challenges of the department ad assess its effectiveness. Conclusion and recommendations were made to the department and how it can improve on its effectiveness in curbing drug abuse in Zimbabwe.